Pengaruh Harga Pelayanan Dan Keselamatan Terhadap Tingkat Kepuasan Mahasiswa Dalam Menggunakan Ojek Online - Aulia, Nabila; Afif Nurdiansyah, Mochamad; Shalihatunnisa, Shalihatunnisa; Christian, Diego; Angeline Seru, Indra; Sifriyani, Sifriyani; Wanti Wulan Sari, Nariza; Yuniarti, Desi; Atarezcha Pangruruk, Thesya; Nadhilah Widyaningrum, Erlyne (EKSPONENSIAL, 2025)
This study aims to analyze the influence of price, service, and safety on the level of satisfaction of FMIPA students at Mulawarman University in using online motorcycle taxi services (Gojek). This study uses a quantitative approach with the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS). A sample of 100 students was obtained through accidental sampling. The variables studied include price, service, safety, and customer satisfaction, each measured by several indicators. The analysis results indicate that the three independent variables (price, service, and safety) have a positive and significant effect on student satisfaction, with safety being the most dominant factor. The R-square value of 0.669 indicates that the model explains 66.9% of the variability in student satisfaction. Validity and reliability tests show that all constructs meet the model's validity criteria. This study suggests that online ride-hailing service providers should prioritize safety aspects, accompanied by improvements in service quality and reasonable price adjustments to enhance user satisfaction.